Stunting control factors related to the occurrence of diarrhea in children in the work area of the Bukit Timah Health Center - Rifa Yanti; Riski Novela Yenita; Faradilla Faradilla (Riset Informasi Kesehatan, 2022)
The mortality rate (CFR) during outbreaks of diarrhea in Indonesia is expected to be <1%. However, diarrhea from 2010 to 2017 found that the CFR during outbreaks was still quite high (>1%).The purpose of this researchThis study aims to determine the factors associated with the incidence of diarrhea in children under five at the Bukit Timah Health Center, Dumai City.This research isstudyanalyticwith a cross-sectional design.The research was conducted at Bukit Timah Health Center.The research population is 120 peoplegwith 93 samples.The statistical test used in this study was the Chi Square test with a 95% confidence level.The results of the analysis show aThere is a relationship between knowledge (p value = 0.004), food factors (p value = 0.014) with the incidence of diarrhea in children under five at Bukit Timah Health Center, Dumai City and notaThere is a relationship between environmental factors (p value = 0.620), socio-economic (p value = 0.058) with the incidence of diarrhea in children under five at Bukit Timah Public Health Center, Dumai City.It is hoped that Bukit Timah Health Center officers will conduct counseling to increase mother's knowledge about diarrhea in toddlers.